Environmental problem-solving : balancing science and politics using consensus building tools : guided readings and scenario assignments from MIT's training program for environmental professionals - Susskind, Lawrence; Verdini Trejo, Bruno; Gordon, Jessica; Zaerpoor, Yasmin (Anthem Press, 2020)
'Environmental Problem-Solving' presents short excerpts from carefully selected readings, expert commentaries on those readings, assignments, and the best MIT student responses to the assignments and exam questions with excellent student response. The book presents four main models of environmental policy-making: competing theories of environmental ethics; tools for environmental assessment and environmental decision-making; and techniques for public engagement and group decision-making. The book covers the material presented in the semester-long course required of all students enrolled in MIT's Environmental Policy and Planning Specialization.